Hyönteisvälitteiset sukkulamadot (Filarioidea) porolla Suomessa – kirjallisuuskatsaus - Havela, Emmaleena; Oksanen, Antti; Laaksonen, Sauli (Suomen eläinlääkäriyhdistys, 2024)
The most common insect-borne nematode parasites of reindeer in Finland are Setaria tundra, Rumenfilaria andersoni and Onchocerca tarsicola. These parasites are new for reindeer and likely resettled by host switching from other cervids since 1970’s. Reindeer have not adapted to these parasites and that is why they cause pathological changes in tissues of a new host species. These parasites have caused several outbreaks in the Finnish reindeer herding area. In addition, Lappnema auris has been discovered rarely in Finland. Insect-borne parasites deteriorate reindeer welfare, decrease calves’ carcass weight and cause condemnations at meat inspection. Among other things, efficient insect transmission and ivermectin resistance make the prevention of these parasites difficult. Through systematic antiparasitic treatment, predicting outbreaks and slowing down climate change it is possible to decrease the impact of these parasites on the welfare of reindeer and on reindeer husbandry. Of the parasites discovered in Finland, the prevention of S. tundra is based on regular and extensive antiparasitic treatment of reindeer. Rumenfilaria andersoni and probably Onchocerca spp. are resistant to ivermectin and therefore cannot be prevented by routine antiparasitic treatment. It is almost impossible to affect the number of insects. Climate change is predicted to increase the spread of insect-borne parasites and enable the parasites to spread into native areas further North. Peer reviewed